How conscieous are you of others? Further evidence on relative income and happiness - Sun Youn Lee; Fumio Ohtake (Osaka University, Institute of Social and Economic Research (ISER), 2018)
Extant research has found that an individual's happiness is relative with respect to income, suggesting that it rises with own income and falls as the income of a reference group increases. Some recent studies emphasize that the effect of relative income is mediated by the extent to which people compare themselves with others (hereinafter, "relative consciousness"). Using the survey data of representative sample of Japan and the U.S., this paper extends the existing literature by providing a statistical evidence that underlines the importance of the intensity of relative consciousness in association with the perception of reference-group income in determining an individual's happiness and his/her decision in line with the maximization of the utility. First, we find people who are highly conscious of others' living standards are unhappier in Japan but happier in the U.S. This opposite effect between the two countries is also found to exist when the same estimation is conducted with panel data. Second, the positive relationship between relative consciousness and happiness found in the U.S. results from the perception of reference-group income: highly conscious people compare downward in the U.S. Lastly, we further examine the extent to which the integrated effect of relative consciousness and reference-group income is related to an individual's decision that could affect the degree of happiness. We discuss how our results can drive a wedge between choice behavior and happiness maximization and thus between happiness and decision utility.
Keywords: D6; I31; J0; 330; Happiness; relative income; relative consciousness; utility